The Developer’s Right to Enforce a Reversionary Right due to the Failure of the Buyer to Erect Dwellings Within a Prescribed Period: A Real or Personal Right? Bondev Midrand (Pty) Ltd v Puling and Another and a Similar Case 2017 (6) SA 373 (SCA) - Maphuti Tuba (Obiter, 2019)
The SCA, in Bondev Midrand (Pty) Ltd v Puling and Another and a Similar Case (2017 (6) SA 373 (SCA)) (Bondev v Puling), made significant pronouncements on whether a right to claim a re-transfer of immovable property (commonly known as a reversionary right) has prescribed in terms of the Prescription Act (68 of 1969) in circumstances where a buyer has failed to erect dwellings within a prescribed period. In response to one of the defences to this claim, it had to decide whether such a reversionary right is a real or personal right. In order to come to its decision, the SCA also referred to the question whether the reversionary right violates the constitutional right not to be arbitrarily deprived of property as well as of the right to have access to adequate housing. More importantly, it had to determine whether a condition incorporating a right to claim a re-transfer of immovable property could be separated into two rights, one constituting a real right, and another a personal right. The purpose of this note is to critically discuss the case in Bondev v Puling. The discussion seeks to critically analyse the correctness of the court’s decision in applying the established test for registration of conditions in terms of section 3(1)(r) read with section 63(1) of the Deeds Registries Act (47 of 1937) (DRA). This note also questions the SCA’s decision that it is possible to separate a condition in the title in order to determine whether parts thereof are real or personal. Before embarking on this discussion, the facts of the case, as well as the issues and decision will be discussed.